Multifunctional and bioinspired titanium surface with multilayer nanofilms for novel dental implant applications - Caiyun Wang; Ran Lu; Xu Cao; Yanting Mu; Su Chen (Frontiers in Chemistry, 2024)
Introduction: Smart multifunctional surfaces targeting intricate biological events or versatile therapeutic strategies are imminent to achieve long-term transmucosal implant success.Methods: This study used dopamine (DA), graphene oxide (GO), and type IV collagen (COL-IV) to construct multilayer nanofilms (DGCn) based on their universal adhesive and biomimetic properties to design a versatile and bioactive titanium implant. The characterization of DGCn on different titanium surfaces was performed, and its loading capacity, release profile, in situ gene delivery, and in vitro biological properties were preliminarily evaluated.Results: Our results demonstrate that hydrogenated TiO2 nanotubes (H) provide a better platform for the DGCn coating than machined Ti and air-TiO2 nanotubes. The H-DGC10 displayed the most stable surface with excellent loading capacity, sustained-release profile, and in situ gene transfection efficiency; this could be due to the high specific surface area of H and GO, as well as the functional groups in H, DA, and GO. Moreover, the H-DGC10 exhibited good biocompatibility for human oral epithelial cells and promoted the expression of integrin β4 and laminin 332, both being hemidesmosome-related proteins.Discussion: Our findings suggest that H-DGCn can be designed as a smart multifunctional interface for titanium implants to achieve long-term transmucosal implant success and aid in versatile therapeutic strategies.